Experimental of Hot Machining for Stainless Steel 316L Cutting Process - Cholis, N.; M. A. H., Yusoff; Lim, S. K.; Ahmad Razlan, Yusoff (Springer, 2024)
Stainless Steel 316L having excessive tensile power and resistance to temperature with excessive manganese content resulting high roughness during cutting process. The problem occurs when machining process conduct at hot conditions to soften the workpieces. To study the cutting parameters effect on surface quality and tool wear length, different temperatures were used for turning process in this study. The experiment conducted with hot machining process at temperature conditions at 200, 300 and 400 °C. The parameters of this experiment are cutting speed of 76–149 mm/min and feed rate of 0.11–0.22 mm/rev with constant value of depth of cut. The results showed the surface roughness affects the tool wear when machining at high feed rate and cutting speed compared to lower parameters conditions. The heating source temperature affects the surface roughness, area roughness parameter and tool wear in cutting process. In conclusion, the surface quality and tool wear improved at high feed rates and cutting speeds compared to lower parameters settings.